Mathematical modeling of the military operation - Pincevičius, Albertas; Rakauskas, Rimantas-Jonas; Misevičius, Gintautas (Lietuvos matematikos rinkinys, 2000)
The aim of this paper is show how the systems of differential equations may be applied both to describe the battle actions between the regular army and the partisans. We adapted the theory to the real situation of the battle actions.